KARAKTERISTIK KEBAHASAAN GENDER DALAM FILM AIR MATA DI UJUNG SAJADAH - Adeliya Sindi; Helmi Seftiani; Sigit Andi Prasetya Dinata (CV. Denasya Smart Publisher, 2024)
The aim of this research is to create different views on the two genders' linguistic characteristics, so that in language they are both seen as having different characteristics. So basically language, gender and culture are related. In society, women are seen as gentle and emotional, while men are seen as firm and strong. Not only are women gentle and emotional, women are also known to often say things that contain uncertainty. In expressing this uncertainty, women often use a syntactic tool called a tag question. It could be said that the women and men who often use tag questions are women (Hidayati, 2016:12). This proves that men are more confident in what they say than women. Tag questions are used by women to confirm what they are saying to their interlocutor (Hidayati, 2010:11). From the explanation above, it indicates that linguistic characteristics can be found in films.